The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s41936-018-0036-4
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological studies on commercial hair dye brand commonly used in Saudi Arabia: histological study of the liver, kidney, heart, and testis

Abstract: Background: Hair dye is commonly used in the Kingdom of Saudi Arabia (KSA). Poisoning occurs when someone swallows dye or tint used to color hair and is considered one of the most significant causes of intentional self-harm. Commercial hair dye may contain varying amounts of paraphenylenediamine and even undeclared chemical ingredients. Therefore, the aim of this study was to evaluate the organ toxicity of commercial hair dye in rats. Acute toxicity study: The commercial hair dye X was orally administered to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Studies have concentration of serum Alkaline phosphatase suggested various side effects of hair dye which (ALP) and Aspartate Amino transferase of the four include skin irritation and allergy, liver disease, test groups were significantly raised (P<0.05) heart and kidney diseases (Sosted et al, 2004; when compared with control. This outcome Bouillon et al, 2005;Amy, 2013;Al-Shaikh et agreed with previous reports (Spector, 1955 andal., 2018). A research done by MADESAFE El-Amin et al,2014) which indicated a (2019) also reported asthma, eye, vertigo, significantly raised ALP and AST after oral and convulsions, and coma as some of the side effects subcutaneous administration of hair dye in Albino of exposure to hair dyes.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have concentration of serum Alkaline phosphatase suggested various side effects of hair dye which (ALP) and Aspartate Amino transferase of the four include skin irritation and allergy, liver disease, test groups were significantly raised (P<0.05) heart and kidney diseases (Sosted et al, 2004; when compared with control. This outcome Bouillon et al, 2005;Amy, 2013;Al-Shaikh et agreed with previous reports (Spector, 1955 andal., 2018). A research done by MADESAFE El-Amin et al,2014) which indicated a (2019) also reported asthma, eye, vertigo, significantly raised ALP and AST after oral and convulsions, and coma as some of the side effects subcutaneous administration of hair dye in Albino of exposure to hair dyes.…”
Section: Discussionsupporting
confidence: 90%
“…Permanent hair dyes are the most popular, accounting for 70% of all hair dyes used [11][12][13] . In a cross-sectional study about hair dye conducted in Saudi Arabia, 82.6% of participants had dyed their hair at some point in their lives [14] . Furthermore, 69.3% had dyed their hair in the last 12 months, with 76.8% using permanent dyes [14] .…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study about hair dye conducted in Saudi Arabia, 82.6% of participants had dyed their hair at some point in their lives [14] . Furthermore, 69.3% had dyed their hair in the last 12 months, with 76.8% using permanent dyes [14] . The defined routine of coloring or dyeing hair at home has been reduced, and there has been an increase in visiting salons for coloring hair [7] .…”
Section: Discussionmentioning
confidence: 99%
“…According to International Agency for Research on Cancer (IARC), some in vitro and in vivo studies on exposed human subjects have shown that some HDs and various chemicals used in HDs are mutagenic or carcinogenic [ 5 ]. According to several studies, PPD causes blood, breast, and bladder cancer in humans and other mammalian species [ 6 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%